Model Desain Healing Garden pada Ruang Publik dan Penataannya pada Halaman Rumah Tinggal bagi Peningkatan Kualitas Hidup di Perumahan Bumi Telukjambe, Karawang: Healing Garden Design Model in Public Spaces and Its Arrangements on the Household Page for Increasing the Quality of Life in Bumi Telukjambe Housing, Karawang - Ina Krisantia; Qurrotu Aini Besila; Silia Yuslim; Riana Ayu Kusumadewi; Nur Intan Mangunsong; Olivia Seanders; Reza Fauzi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Bumi Telukjambe Housing, Karawang is a Perumnas (National Housing) area dominated by 21/60 house types. Houses with a limited area and the COVID19 pandemic create boredom and stress for residents because almost all of the resident's time is spent working at home. To minimize the feeling of boredom and stress of residents, efforts are needed to overcome them. Many studies reveal that one way to improve mental health and quality of life is to connect with nature. Healing garden is one way to make it happen. Community Service (Program Pengabdian kepada Masyarakat, PkM) of Department Landscape Architecture will conduct counseling on healing gardens, training on healing gardens on residential yards, and create a design model Healing Garden in public spaces to be used jointly by residents. The benefits felt by residents from PkM activities can be seen from questionnaires distributed to PkM participants, namely representatives of the Family Welfare Guidance Programme (Pembinaan Kesejahteraan Keluarga, PKK) women and RW/RT representative (RW 19’s Chief and RT 04’s Chief). The results of this PkM show that from all the statements answered by the participants, 100% of the participants felt that all the PkM activities they carried out were beneficial.